2014
DOI: 10.1002/pssa.201300721
|View full text |Cite
|
Sign up to set email alerts
|

InSb:Mn – A high temperature ferromagnetic semiconductor

Abstract: Diluted magnetic semiconductor InSb:Mn exhibits a ferromagnetic behavior up to T ∼ 600 K due to presence of nanosize MnSb precipitates [Kochura et al., J. Appl. Phys. 113, 083905 (2013)]. Transport properties of InSb:Mn, including the resistivity, the magnetoresistance (MR), and the Hall effect, are investigated between T ∼ 1.6 and 300 K in magnetic fields B up to 15 T. The resistivity, ρ(T), displays an upturn with lowering the temperature below T ∼ 10–20 K attributable to the Kondo effect, where the universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, it has been shown that already in the pure as-grown ZnSnAs 2 film the observed dependences of µ(T) and p(T) satisfy reasonably those of the two-band conduction mechanism, taking into account the holes in the valence band and in the acceptor band [26]. It is worth mentioning the two-band conduction, observed in the II-V semiconductor CdSb [27] and in the III-V based In 1-x Mn x Sb [28], permitting a detailed quantitative explanation of the resistivity and the Hall effect data in strong magnetic fields. The situation with the transport data in the ZnSnAs 2 + MnAs samples at this point is even more complicated than in a pure ZnSnAs 2 compound, suggesting existence of an additional conduction channel or additional type of carriers, associated with MnAs inclusions and having concentrations and mobilities, which differ drastically from those in the pure ZnSnAs 2 compound.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 56%
“…On the other hand, it has been shown that already in the pure as-grown ZnSnAs 2 film the observed dependences of µ(T) and p(T) satisfy reasonably those of the two-band conduction mechanism, taking into account the holes in the valence band and in the acceptor band [26]. It is worth mentioning the two-band conduction, observed in the II-V semiconductor CdSb [27] and in the III-V based In 1-x Mn x Sb [28], permitting a detailed quantitative explanation of the resistivity and the Hall effect data in strong magnetic fields. The situation with the transport data in the ZnSnAs 2 + MnAs samples at this point is even more complicated than in a pure ZnSnAs 2 compound, suggesting existence of an additional conduction channel or additional type of carriers, associated with MnAs inclusions and having concentrations and mobilities, which differ drastically from those in the pure ZnSnAs 2 compound.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 56%
“…Negative magnetoresistance (NMR) was observed in InSb crystals at low temperatures and weak magnetic fields [1][2][3][4][5][6][7][8][9]. There are various interpretations of this effect due to different mechanisms of scattering of charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…There are various interpretations of this effect due to different mechanisms of scattering of charge carriers. In particular: 1) surface boundary scattering [1,2]; 2) scattering on magnetic impurities [3][4][5]; 3) scattering on nonmagnetic impurities with concentration in the vicinity to metal-insulator transition (MIT) [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrate ferromagnetism and spin-depended scattering above the room temperature. An influence of the ferromagnetic MnSb inclusions on magnetic and electrical properties of InSb/MnSb nanostructures was observed both in bulk [15][16][17] and in films [18,19].…”
Section: Introductionmentioning
confidence: 99%